Design and Analysis of Front Side Modular Multilevel Converter for Smart Transformer in 15 kV Arba Minch Distribution Network Using Diverse Controllers and Multicarrier Modulation - Yalisho Girma Loaena; Ing. Getachew Biru; Chandra Sekha Reddy (Journal of Engineering)
This paper presents design and analysis of a bidirectional medium voltage (MV) front-side converter of smart transformer (ST) for Arba Minch Town distribution system. A modular multilevel converter (MMC) configuration is used in the MV side of the ST. The grid side MV is 15 kV RMS line value and the desired MVDC voltage is 24.5 kV for ensuring bidirectional operation of the converter in the time of grid outage. A half bridge semiconductor power module is used to model the front-side MMC. Based on the MV DC voltage requirement, the number of submodules per phase leg is designed to be four (four in the upper arm and four in the lower arm). Multicarrier modulation techniques such as phase-shifted PWM and level-shifted PWM are used to generate gate signals. The model is developed in MATLAB/Simulink, and its performance with respect to input side voltage harmonics, current harmonics, and output DC voltage value has been tested by carrying out several case studies under different controllers such as proportional integrator(PI), fuzzy inference system (FIS), and adaptive neuro fuzzy inference system (ANFIS) for obtaining reference signal for modulation. Level-shifted PWM is used with PI, FIS, and ANFIS, whereas phase-shifted PWM with a technique of introducing DC bias is used with PI controller alone. From the simulation results, it has been observed that better power system current quality of FS-MMC is obtained for PS-PWM (2.16%) than level-shifted PWM (5.22%). Use of FIS and ANFIS with level shift PWM method slightly brings down the current THD values to 2.98% and 2.72%, respectively (decrease by 2.5%). Also, a maximum output DC voltage of 24650 V is obtained for ANFIS with level shift PWM as compared to values obtained by PI with level shift PWM and PI with phase shift PWM.